2013
DOI: 10.1021/bi400502c
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Unfolding of Compact Conformations of the Intrinsically Disordered Protein Osteopontin

Abstract: Intrinsically disordered proteins (IDPs) constitute a class of biologically active proteins that lack defined tertiary and often secondary structure. The IDP Osteopontin (OPN), a cytokine involved in metastasis of several types of cancer, is shown to simultaneously sample extended, random coil-like conformations and stable, cooperatively folded conformations. By a combination of two magnetic resonance methods, electron paramagnetic resonance and nuclear magnetic resonance spectroscopy, we demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
122
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 45 publications
(103 reference statements)
6
122
0
14
Order By: Relevance
“…While detailed characterization and analysis of the DEER time traces of the OPN apo state have already been reported, [11] here the DEER data were recorded in the absence and the presence of heparin. All DEER data are shown in the Supporting Information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While detailed characterization and analysis of the DEER time traces of the OPN apo state have already been reported, [11] here the DEER data were recorded in the absence and the presence of heparin. All DEER data are shown in the Supporting Information.…”
mentioning
confidence: 99%
“…[11] D eff denotes the total signal decay at the experimental DEER evolution time (see the Supporting Information) and is an approximate measure of the average interspin distance for broad P(R) distributions. [11] For increasing interspin mean distance R between two labeling sites D eff typically decreases.…”
mentioning
confidence: 99%
“…Such partially unfolded/misfolded intermediates are populated under denaturing conditions. Contrary to this belief, recent studies have shown that denaturation of IDP Osteopontin (OPN), lead to formation of extended, random coil-like conformation and stable, cooperatively many folded conformation [14] . Further, these IDPs are associated with human diseases, including cancer, cardiovascular disease, amyloidoses, neurodegenerative diseases, and diabetes.…”
Section: Introductionmentioning
confidence: 89%
“…Some IDPs gain structure upon binding and undergo a disorder-to-order transition [32][33][34], while other observations support the existence of 'fuzzy complexes' where such transitions do not occur [35]. The latter was the case for a fuzzy complex with an OPN fragment, where an increase in disorder was observed when bound to heparin [36]. OPN has been called a molecule for all seasons [37].…”
Section: Introductionmentioning
confidence: 99%
“…Fisher et al [10] determined, using 1-D 1 H NMR and transverse relaxation times, that the solution structure of native OPN was consistent with that of an IDP. Kurzbach [36] combined electron paramagnetic resonance (EPR) and NMR techniques to show that different OPN compact and extended conformations can interconvert through cooperative phase transitions. Yamaguchi et al [43] have shown that recombinant mouse OPN exhibits a transient long-range intramolecular interaction between its N-and Cterminal regions that can shield the central part of the chain from integrin interactions.…”
Section: Introductionmentioning
confidence: 99%